1967
DOI: 10.1128/jb.93.2.740-748.1967
|View full text |Cite
|
Sign up to set email alerts
|

Episome-carried Surface Antigen K88 ofEscherichia coliIII. Morphology

Abstract: Two nonfimbriate strains of Escherichia coli and their K88+ counterparts, obtained by episomal transfer of this antigen, were studied with the electron microscope. Specimens were prepared with the spray drop method and were studied after shadow-casting. Under these conditions, the alteration in surface structure, due to the acquisition of K88 antigen, appeared as a fur of fine filaments, distinctly more flexible than fimbriae. Purified K88 antigen was also studied and found to have the same structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
1

Year Published

1974
1974
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(61 citation statements)
references
References 18 publications
1
59
0
1
Order By: Relevance
“…Filters were washed and reacted with hydrogen peroxide substrate and 4chloronaphthol chromogen. The immunological detection of CS31A was controlled by SDS-PAGE analysis of extracts obtained by heating the bacterial suspensions at 60°C for 20 min [10]. After silver staining of the gel, the 29K CS31A fimbrial subunit was identified [5].…”
Section: Detection Of Firnbrial Antigens F165 and Cs31amentioning
confidence: 99%
“…Filters were washed and reacted with hydrogen peroxide substrate and 4chloronaphthol chromogen. The immunological detection of CS31A was controlled by SDS-PAGE analysis of extracts obtained by heating the bacterial suspensions at 60°C for 20 min [10]. After silver staining of the gel, the 29K CS31A fimbrial subunit was identified [5].…”
Section: Detection Of Firnbrial Antigens F165 and Cs31amentioning
confidence: 99%
“…This attribute is recognized as a fundamental feature of the bacterial intestinal pathogens that infect and cause acute diarrhoea in piglets, calves, lambs and humans (Gaastra & deGraff 1982). The attachment of the pathogen to the mucosa of the small intestine in these species is mediated by antigenically distinct bacterial surface adhesions (Brinton 196.5;Stirm et al 1967;Jones & Rutter 1972;Smith & Linggood 1972;0rskov etal. 197.5;Evans & Evans 1978;Isaacson et al 1978;Morris et al 1982), morphologically identified as fimbriae or pili (Duguid & Anderson 1967).…”
Section: Introductionmentioning
confidence: 99%
“…The colonization factor antigens of E. coli resemble the type 1 pili morphologically, but cause mannose-resistant agglutination ofhuman and bovine erythrocytes (11,12). K88 and K99 are pilus-like antigens on the E. coli strains enteropathogenic for pig, calf, and lamb (17,36,37). The significance of the pili for bacterial survival and pathogenicity in vivo is uncertain.…”
mentioning
confidence: 99%